The impacts of COVID-19 on cattle traders and their response in agro-pastoral and pastoral regions in Uganda: A case of Karamoja and Teso cattle traders - John Ilukor; Akello Joyce; Simon Peter Okiror (Springer Berlin Heidelberg, 2022)
The study assessed the economic impact of COVID-19 on cattle traders in the Karamoja and Teso pastoral and agro-pastoral areas in Uganda and their response after the COVID-19 lockdown in 2020. The results reveal that cattle traders were negatively affected by COVID-19 in many ways including reduction in cattle sales, erosion in operating capital, and failure to sell animals while others have diversified or moved to other businesses. Twenty-five per cent of the cattle traders did not sell any animal during the lockdown. A majority of these were from Karamoja (43%) compared to those in Teso sub-region. The decline in cattle sales was significantly higher in Karamoja than in Teso sub-region. However, their recovery was significantly higher in Karamoja than in Teso sub-region because traders in Teso greatly diversified to other economic activities compared to traders in Karamoja sub-region. The traders who lost capital were mainly in Teso sub-region (63%). As expected, there was a sharp decline in the number of cattle buyers from markets outside the study area, mainly from Juba, Kampala, Busia, and Kenya. Coping strategies by cattle traders included crop cultivation (80%), burning charcoal (15%), selling food items (8%), and boda-boda riding (12%), while others did not engage in any economic activity (25%). To mitigate against the pandemic, traders were observing some of the standard operating procedures (SOPs) such as wearing face masks (76.1%), handwashing (19.3%), sanitising (2.3%), and social distancing (2.3%). Traders from Karamoja performed poorly in both diversification and mitigation measures. Based on our findings, recommendations to mitigate the impact of COVID-19 on cattle traders include offering loans to cattle traders through their Village Savings and Loan Association (VSLA), reducing transaction costs, offering mobile phones especially for Karamoja traders, and promoting the adoption of enforcing SOPs to reduce the need for lockdowns and cattle market closures which are detrimental to pastoral livelihood.
Keywords: Agro-pastoral, Pastoral, Cattle traders, COVID-19, Karamoja, Teso